Optimization of Tilt Angle for Fixed Tilt Solar PV System: Case Study for USIM, Nilai, Negeri Sembilan - M. K. F. Ahamad; Khairi bin Abdulrahim (Penerbit Universiti Teknikal Malaysia Melaka Press, 2026)
Indexed by MyCite